PELAKSANAAN PERNIKAHAN SANTRI (ABDI NDALEM) DI PONDOK PESANTREN BAITUL MUSTAQIM - Anggita Vela; Muhammad Sirojudin Sidiq; Andi Ali Akbar; Lulu Arini (LPPM STAI DARUSSALAM LAMPUNG, 2024)
This research aims to find the factors of marriage of indentured servant students carried out at the BaitulMustakim Islamic Boarding School, the contribution of the Kyai Caretaker of the Islamic Boarding School given to his indentured servant students, and the legal certainty of marriages carried out by indentured abdindalem. The method used in this research is field research, using a qualitative descriptive approach. Data collection uses the interview method. With the research location at the BaitulMustakim Islamic Boarding School, Punggur District, Central Lampung Regency, Lampung Province. Those examined were Islamic boarding school caretaker kyai, Ustad-Ustadzah, abdindalem students who held weddings at the Islamic boarding school. The findings of this study are that the marriage of santriabdindalem carried out at the Boarding School is due to several factors including; the offer from the Kyai Caretaker of the Islamic Boarding School, the desire of the parents of Santriabdindalem, the desire of santri to carry out marriages at the Boarding School. The contribution given by the Kyai Caretaker of the Islamic Boarding Schoolto the santriabdindalem towards the implementation of marriages held at the Boarding School is to provide assistance in the marriage registration process, money or 5 grams of gold, consumption. That the marriage carried out by the santriabdindalem is legally valid according to religion and the state.